Incidence of Emergence Agitation in Pediatric Patient after General Anesthesia - Andriyanto, Lucky; Utariani, Arie; Hanindito, Elizeus; Santoso, Kohar Hari Santoso Hari; Hamzah, Hamzah; Puspita, Eka Ari (Folia Medica Indonesiana, 2019)
Post anesthesia agitation is common problem in pediatric post anesthesia care unit. The incidences range from 10 to 80%. EA has been described as a dissociated state of consciousness in which the child is inconsolable, irritable, and uncooperative typically thrashing, crying, moaning or incoherent. This study was done to determine the incidence of emergence agitation and associated risk factors in pediatric patients who underwent general anesthesia. This descriptive and analytic study was performed on 105 pediatric patient aged 1-12 years that underwent general anesthesia for various elective diagnostic and surgeries at Dr. Soetomo Hospital between January and February 2016. The presence of emergence agitation was recorded using Pediatric Anesthesia Emergence Delirium (PAED) scale. The factors that linked with Emergence Agitation were recorded in a questionnaire. The data were analyzed using SPSS software with logistic regression. p - values less than 0.05 were considered as significant. Forty two (40%) children had Emergence Agitation. Preoperative anxiety (p = 0.006) and Pain (p=0.035) were associated with higher rates of post anesthetic emergence agitation. This study identified preoperative anxiety and pain as risk factors, which are associated with emergence agitation in children. To minimize the incidence of post anesthetic emergence agitation, these risk factors should be considered in the routine care by anesthetist.